Injuries in martial arts and combat sports: Prevalence, characteristics and mechanisms - Del Vecchio, F. B.; Farias, C. B.; de Leon, R. C.; Rocha, A. C. C. A.; Galliano, L. M.; Coswig, V. S. (Science & Sports, 2018)
Objective: To measure sports injuries prevalence, types and mechanisms, considering grappling and impact modalities.